Multiobjective Distribution Network Reconfiguration Considering the Charging Load of PHEV - Li, Gaowang; Shi, Dongyuan; Duan, Xianzhong (Elektronika ir Elektrotechnika, 2013)
Energy crisis and environmental pollution make the plug-in hybrid electric vehicle (PHEV) become a hot topic. This paper proposes a multiobjective network reconfiguration methodology based on quantum-inspired binary particle swarm algorithm that aims at alleviating the adverse impact of PHEV on distribution system. The methodology involves two steps: load level division and network reconfiguration for each load level. Two different charging patterns of PHEV are considered in this analysis: uncoordinated charging and coordinated charging. The simulation results show that the proposed methodology is an effective method to make the distribution network more flexible to accommodate PHEV. DOI: http://dx.doi.org/10.5755/j01.eee.19.5.1738